Faculty as bridges to co-curricular engagement and community for first-generation international students. Issue 5 (4th May 2017) - Glass, Chris R.; Gesing, Peggy; Hales, Angela; Cong, Cong
Abstract : The proportion of first-generation international students at US institutions ranges from one-tenth to one-half of the total international student body. First-generation status is an underexplored, and potentially significant, demographic factor in international students' adaptation to college. Researchers used structural equation modelling (SEM) to examine how faculty interaction out-of-class, engagement with cultural variation in-class, and students' interest in cross-cultural interaction relates to sense of community and co-curricular engagement among first-generation ( n  = 508) and non-first-generation ( n  = 955) international students', respectively. The primary contribution of this study is providing evidence for the importance of interactions with professors out-of-class and engagement with cultural variation in-class on international students' sense of community and co-curricular engagement, especially first generation students. Implications for research and practice are discussed.